Home and the Limits of Individualization: Imbalance Between Personal, Statutory, and Belonging spaces - Maunaye, Emmanuelle; Ramos, Elsa (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2022)
Research context : This article takes on the point of view that places the focus on the individual, despite belonging within a family group, and explores the concept of home as a space that contributes to the formation of an “individualized individual,” but that also takes into account the possible limits of this function of home. Objectives : This overview aims to define the concept of home in order to identify all of its dimensions. While the spatial, temporal and relational dimensions of home can be distinguished for the purposes of analysis, on the one hand, the article aims to show how they are intimately articulated in the experiences of individuals to support the construction of their personal identity, their autonomy, their self-empowerment and their relationship to location or place (Simard and Savoie, 2009); and how they are closely linked in the construction of groups and family relationships. Methodology : This article is based on a literature review and on the contributions to this issue to present the concept of home and the theoretical perspective taken. Results : In family, marital and intergenerational cohabitation, the construction of home is played out in interaction with other family members, who also have their own constructions and conceptions of home. These constructions and understandings produce differentiated and sometimes asymmetrical relationships, as well as three different experiences of home. The first refers to personal spaces, “at my home”; the second, to the rules and laws that govern cohabitation and the space in which home is located. In this case, it is defined by a statutory and hierarchical aspect, and the individual has a place assigned by his status. This is designated as “at my parent’s home.” The third is represented by belonging and by a place in a group or community where the individual is considered equal. This is belonging to “our home”. If the first “home” is the main factor in the process of individualization, so are the other two: one explains the boundaries of the “home,” and the other, the individual's belonging to the group, especially the family. Conclusions : The question of home leads to two aspects: the relationship with home of the sole inhabitant and the relationship with home of the inhabitant together with others . In this second aspect, there is a tension between a logic of autonomy and a logic of belonging as a member of the group. Being a member of the group, interpreted as being at our home, has two dimensions: being assigned to our home and belonging to our home. In this sense, our home acts as a constraint on the concept of home, and the family appears to be a paradoxical validation of the individual. Thus, the family has a dual function: to make it possible to be oneself (by privileging personal spaces and validating individual dimensions of identity) and to acknowledge that each member belongs to the group and has a place in it . The limits of the individualization of the home become apparent when there is an imbalance among these three aspects of “home”: having a personal space, being assigned within our home, and belonging to our home. Contribution: Home is a valuable perspective in this construction, which links the past, present and future: having been, being and becoming. The iterative movement between home and identity is central to the formation of the individual and the family group.